2020
DOI: 10.1007/s11064-020-03010-5
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole Reduces zif-268 mRNA Expression in Brain Structures involved in the Generation of Harmaline-Induced Tremor

Abstract: Essential tremor is one of the most common neurological disorders, however, it is not sufficiently controlled with currently available pharmacotherapy. Our recent study has shown that pramipexole, a drug efficient in inhibiting parkinsonian tremor, reduced the harmaline-induced tremor in rats, generally accepted to be a model of essential tremor. The aim of the present study was to investigate brain targets for the tremorolytic effect of pramipexole by determination of the early activitydependent gene zif-268 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…Pramipexole also reduced the level of harmaline-increased expression of zif-268 mRNA in the ION, cerebellar cortex, and motor cortex. These results obtained by the authors [ 140 , 177 ] confirmed the beneficial effects of pramipexole, a registered anti-parkinsonian drug, in the harmaline model of ET and its potential role in ET therapy. In addition, the attenuation of the harmaline-induced activity of the ION, cerebellar cortex, and motor cortex may be important in the tremorolytic effect of pramipexole, although the exact neuronal mechanisms underlying the drug action are unfortunately still unclear.…”
Section: The Dopaminergic System and Dopamine Receptors—the Role In Etsupporting
confidence: 62%
See 3 more Smart Citations
“…Pramipexole also reduced the level of harmaline-increased expression of zif-268 mRNA in the ION, cerebellar cortex, and motor cortex. These results obtained by the authors [ 140 , 177 ] confirmed the beneficial effects of pramipexole, a registered anti-parkinsonian drug, in the harmaline model of ET and its potential role in ET therapy. In addition, the attenuation of the harmaline-induced activity of the ION, cerebellar cortex, and motor cortex may be important in the tremorolytic effect of pramipexole, although the exact neuronal mechanisms underlying the drug action are unfortunately still unclear.…”
Section: The Dopaminergic System and Dopamine Receptors—the Role In Etsupporting
confidence: 62%
“…In the following study, Kosmowska et al [ 140 ] searched for brain structures involved in the tremorolytic effect of pramipexole and determined the expression of the early activity-dependent gene, zif-268 mRNA, by in situ hybridization. They found that harmaline increased both the tremor and expression of zif-268 mRNA in the IO, cerebellar cortex, ventral nuclei of the thalamus, and motor cortex [ 140 ]. Pramipexole reversed the harmaline-induced tremor and there was an increase in zif-268 mRNA expression in all the structures examined except for the ventral thalamic nuclei [ 140 ].…”
Section: The Dopaminergic System and Dopamine Receptors—the Role In Etmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized above, convergent input from anatomical, pharmacological, and neurochemical studies have strongly implicated the enhancement of GABAergic neurotransmission through GABA-A receptors as an important anti-tremor mechanism both in ET and PD [35,38,46,[51][52][53][54][55]. Although enhanced inhibition by GABA-A receptor PAMs that non-selectively interact with α1, α2, α3, and α5 subunits produces anti-tremorogenic effects, such PAMs are also associated with sedation, ataxia, tolerance development, memory impairment, and abuse liability [56].…”
Section: Gaba-a α2/3 Subunit Specific Receptors As Novel Drug Targets...mentioning
confidence: 99%